(untitled) (International Journal of Engineering and Computer Science, 2017)
In this age of universal electronic connectivity when world is becoming a global village ,different threats like viruses and hackers, eavesdropping and fraud, undeniably there is no time at which security does not matter. In view of large growing population of vulnerabilities, major challenge is how to prevent exploitation of these vulnerabilities by attackers. The first step in understanding vulnerabilities is to classify them into a taxonomy based on their characteristics. A good taxonomy also provides a common language for the study of the field. Properties and requirements of good taxonomy are described in this paper to lead security experts for the development of secure infrastructure. An analysis of some prominent taxonomies and their valuable aspects are highlighted that can be used to create a complete useful taxonomy.